Artocarpus tonkinensis Extract Inhibits LPS-Triggered Inflammation Markers and Suppresses RANKL-Induced Osteoclastogenesis in RAW264.7 - Orecchini, Elena; Mondanelli, Giada; Orabona, Ciriana; Volpi, Claudia; Adorisio, Sabrina; Calvitti, Mario; Thuy, Trinh Thi; Delfino, Domenico V.; Belladonna, Maria Laura (Frontiers in Pharmacology, 2021)
Artocarpus tonkinensis (At) leaf decoction, a traditional remedy prepared in North Vietnam by the Hmong ethnic group, is a tea extract rich in bioactive compounds that may have therapeutic effects in arthritis and backache. Indeed, it has been demonstrated that At is able to inhibit Th17 lymphocytes development and to protect mice in an experimental model of collagen-induced arthritis. By resorting to macrophage in vitro models of inflammation and osteoclastogenesis, we showed that At extract significantly reduced nitric oxide synthase 2 (NOS2) activity and IL-6 production by RAW 264.7 murine cells. Moreover, At demonstrated an anti-osteoclastogenic effect, as revealed by complete inhibition of TRAP-positive osteoclast formation and decreased expression of key osteoclast-related genes. This At activity likely relies on the inhibition of RANK downstream signaling pathway, as the activation of non-receptor tyrosine kinase Src is reduced upon RANKL-At exposure. Protective effect of At against bone loss was also enlightened in vivo by collagen-induced arthritis (CIA) experiment demonstrating that, although paw edema was only weakly opposed by drinking At decoction, bone and cartilage were well preserved in CIA+At mice and joint tissue expressed decreased levels of osteoclast marker genes respect to CIA control group. Maesopsin 4-O-β-D-glucoside (i.e., TAT-2, one of the main decoction bioactive components) was capable to contrast NOS2 activity, IL-6 expression and osteoclast formation, too, albeit to a lesser extent when compared to At decoction. Overall, this study enlightens another At cell target, macrophages, beside Th17 lymphocytes, and suggests that the anti-arthritic beneficial effects of At decoction largely derives from its ability to counteract not only inflammation, but also osteoclastogenesis.